MHD Simulations of the ISM: The Importance of the Galactic Magnetic Field on the ISM ``Phases'' - de Avillez, Miguel (2012)
We have carried out 1.25 pc resolution MHD simulations of the ISM, on a Cartesian grid of 0 ≤ (x, y) ≤ 1 kpc size in the galactic plane and −10 ≤ z ≤ 10 kpc into the halo, thus being able to fully trace the time-dependent evolution of the galactic fountain. The simulations show that large scale gas streams emerge, driven by SN explosions, which are responsible for the formation and destruction of shocked compressed layers. The shocked gas can have densities as high as 800 cm^−3 and lifetimes up to 15 Myr. The cold gas is distributed into filaments which tend to show a preferred orientation due to the anisotropy of the flow induced by the galactic magnetic field. Ram pressure dominates the flow in the unstable branch 100 < T ≤ 10^{3.9} K, whereas for T ≤ 100 K (stable branch) magnetic pressure takes over. Near supernovae thermal and ram pressures determine the dynamics of the flow. Up to 80% of the mass in the disk is concentrated in the thermally unstable regime 100 < T ≤ 10^{3.9} K with ∼30% of the disk mass enclosed in the T ≤ 10^{3} K gas. The hot gas in contrast is controlled by the thermal pressure, since magnetic field lines are swept towards the dense compressed walls.